2022
DOI: 10.4055/cios22014
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Traditional Prognosis Scoring Systems and Skeletal Oncology Research Group Nomogram for Predicting Survival of Spinal Metastasis Patients Undergoing Surgery

Abstract: Background Many scoring systems that predict overall patient survival are based on clinical parameters and primary tumor type. To date, no consensus exists regarding which scoring system has the greatest predictive survival accuracy, especially when applied to specific primary tumors. Additionally, such scores usually fail to include modern treatment modalities, which influence patient survival. This study aimed to evaluate both the overall predictive accuracy of such scoring systems and the predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 35 publications
2
7
1
Order By: Relevance
“…Smeijers et al 14 concluded that the SORG nomogram enjoyed a superior performance in survival prediction for surgery in spinal metastases. Although the external validation of the SORG nomogram indicated a superior predictive ability, [33][34][35] the nomogram performed poorly in estimating survival with an accuracy of 0.618 for 90 days, and 0.621 for 365 days in the present study.…”
Section: Discussioncontrasting
confidence: 65%
“…Smeijers et al 14 concluded that the SORG nomogram enjoyed a superior performance in survival prediction for surgery in spinal metastases. Although the external validation of the SORG nomogram indicated a superior predictive ability, [33][34][35] the nomogram performed poorly in estimating survival with an accuracy of 0.618 for 90 days, and 0.621 for 365 days in the present study.…”
Section: Discussioncontrasting
confidence: 65%
“…[7][8][9][10] accurate at predicting the survival of patients with spinal metastasis undergoing surgery. 11 In the same study, we found significant differences in the median survival times between spinal metastases from hematologic malignancies (lymphomas and multiple myeloma) and other solid tumor metastases. Therefore, we hypothesized that spinal metastases caused by hematologic malignancies have different prognostic predictors than those from other solid tumors.…”
Section: Introductionmentioning
confidence: 65%
“…Many scoring systems for predicting the duration of survival have been proposed; however, the accuracy of such scoring systems varies significantly. 11,12 Because most traditional scoring systems were developed on the basis of data analysis from before the modern era of adjuvant treatment and new surgical techniques, they are often inaccurate, especially in terminally ill patients, [13][14][15] as shown in previous studies. [16][17][18] Our previous study showed that the accuracy of the available predictive models differs and demonstrated that the Skeletal Oncology Research Group (SORG) system is the most…”
mentioning
confidence: 99%
“…Moreover, recent studies have shown that surgery with radiotherapy for MSD results in better outcomes, including quality of life, than radiotherapy alone [6,7]. Surgery's role in MSD is appropriately discussed in specific situations because tumor origin sites and patients' conditions differ [16]. Therefore, this study was designed to evaluate the role of surgery compared to radiotherapy alone, confined to patients with thoracic spine metastasis of NSCLC and similar conditions by propensity score matching.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of the surgery was to provide decompression of the spinal cord and stabilization using bone grafting and fixation devices in a palliative setting [2]. The surgical procedures were tailored for each patient depending on the location of the tumors and the patient's condition [16]. In general, anterior corpectomy or posterior vertebral column resection (PVCR) with interbody bone grafting was performed for anteriorly located tumors with vertebral body collapse and spinal instability [17].…”
Section: Procedures Of Surgery and Radiotherapymentioning
confidence: 99%